Detailed Design and Economic Evaluation of a Cryogenic Air Separation Unit with Recent Literature Solutions - Young, André F; Villardi, Hugo G. D; Araujo, Leonardo S; Raptopoulos, Luciano S. C; Dutra, Max S (Industrial & engineering chemistry research, 2021)
Cryogenic air separation is a well-established technology. However, due to its associated energy intensity and hazardousness, new studies are always emerging on this topic. Nevertheless, economic feasibility studies of cryogenic separation plants are still scarce. Studies of this type are essential because installing an air separation unit can also be considered at the design stage of other common industrial projects, such as oxidation/combustion processes and ammonia production. This study aims to elucidate the technical and economic aspects of a real-size air separation unit and analyze the feasibility of incorporating some alternatives recently proposed in the literature, such as multistage compression with and without an organic Rankine cycle for energy saving, integrated argon column, energy recovery systems in turbines, and a PSA unit for CO2 removal, and in the implementation of a new plant. For this, we performed a rigorous simulation and a robust economic evaluation. Thus, it was possible to identify the main bottlenecks of the process, which may become the subject for future work. As a result, the relevance of the compression (34–36%) and refrigeration (54–55%) stages in the capital cost and the importance of conscious electricity (29–32% of the production costs) and maintenance spending for the process’ economic viability were shown. Flowsheets and economic analysis are presented in detail so that they could be used as a base case for future developments in this field.